Limited integrative repair capacity of native cartilage autografts within cartilage defects in a sheep model - Gelse, Kolja; Riedel, Dominic; Pachowsky, Milena; Hennig, Friedrich; Trattnig, Siegfried; Welsch, Götz (Journal of Orthopaedic Research, 2015)
The purpose of this study was to investigate integration and cellular outgrowth of native cartilage autografts transplanted into articular cartilage defects. Native cartilage autografts were applied into chondral defects in the femoral condyle of adult sheep. Within the defects, the calcified cartilage layer was either left intact or perforated to induce bone marrow stimulation. Empty defects served as controls. The joints were analyzed after 6 and 26 weeks by macroscopic and histological analysis using the ICRS II Score and Modified O'Driscoll Scores. Non-treated defects did not show any endogenous regenerative response and bone marrow stimulation induced fibrous repair tissue. Transplanted native cartilage grafts only insufficiently integrated with the defect borders. Cell death and loss of proteoglycans were present at the margins of the grafts at 6 weeks, which was only partially restored at 26 weeks. Significant cellular outgrowth from the grafts or defect borders could not be observed. Bonding of the grafts could be improved by additional bone marrow stimulation providing ingrowing cells that formed a fibrous interface predominantly composed of type I collagen. Transplanted native cartilage grafts remain as inert structures within cartilage defects and fail to induce integrative cartilage repair which rather demands additional cells provided by additional bone marrow stimulation. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:???-???, 2015.
EVALuna2:15819